Method for preparing limestone calcined clay cement based on polyaluminum ferric sulfate

By using polymeric iron aluminum sulfate to replace gypsum in the LC3 cement system, as a quick-setting agent and premature strength agent, the problem of failure to effectively adjust the LC3 hydration rate and improve its mechanical properties in the prior art is solved, and faster settling time, higher strength and better anti-permeability are achieved.

CN119750934AActive Publication Date: 2025-04-04JILIN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411860499.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art has failed to effectively develop efficient and low-cost hydration reaction aids to replace gypsum, adjust the LC3 hydration rate, and improve its mechanical properties and anti-permeability.

Method used

Polymerized ferrous aluminum sulfate is used as flocculant to wash and purify the ball clay, and a mixed powder of calcined ball clay and polymerized ferrous aluminum sulfate is prepared, and it is replaced by gypsum in the limestone calcined clay cement system to serve as a quick-setting agent and premature strength agent to promote the hydration reaction.

Benefits of technology

Through the introduction of polymeric iron aluminum sulfate, the hydration rate of LC3 cement is significantly improved, the settling time is shortened, the early strength is enhanced, the later strength and ion permeability are improved, and the invasion of harmful media is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193089450000071
    Figure BDA0005193089450000071
Patent Text Reader

Abstract

The invention is applicable to the technical field of building materials, and provides a method for preparing limestone calcined clay cement based on polyaluminum ferric sulfate, which comprises the following steps: using polyaluminum ferric sulfate as a flocculant, washing and purifying low-grade ball clay to obtain mixed slurry, and drying, grinding and calcining the mixed slurry to obtain the limestone calcined clay cement. Mixed powder of the calcined ball clay and the polymeric aluminum ferric sulfate is obtained; uniformly mixing the mixed powder, ground heavy calcium carbonate powder and cement clinker to obtain a solid mixture; and mixing the solid mixture with water, uniformly stirring, and curing and forming to obtain the limestone calcined clay cement. In the limestone calcined clay cement, the polyaluminum ferric sulfate is used for replacing gypsum and is used as an accelerator and an early strength agent, so that the hydration rate is increased, the setting time is prolonged, the early strength is improved, and the later strength and the impermeability are enhanced; the method is simple and convenient in process flow, low in raw material price and easy to implement, and promotes the development of a limestone calcined clay cement system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate. Background Art

[0002] Currently, cement production accounts for about 8% of global CO2 emissions, and the International Energy Agency stated in 2021 that by 2050, buildings must achieve net zero carbon emissions throughout their life cycle. Chemical and thermal combustion in the cement production process is the main source of CO2 emissions, of which 60% of emissions come from the process of heating limestone to produce clinker, and the remaining 40% comes from the combustion of fuel in cement kilns (Global Cement and Concrete Association, 2022). 3 ) replacing traditional cement types, the reduction in carbon dioxide emissions can reach 40%.

[0003] LC 3 It is a new type of low-carbon cement with low clinker content, usually composed of limestone, calcined clay, gypsum and clinker. Compared with ordinary Portland cement, LC 3 It has the following advantages: 1) The calcination temperature of cement clinker is higher than that of clay and needs to be carried out at 1450℃, while the calcination temperature of clay only needs to be 600-900℃, and limestone does not need to be calcined. Therefore, replacing cement clinker with these two raw materials can greatly reduce production energy consumption and CO2 emissions; 2) Replacing part of the cement clinker with calcined clay and limestone, the CASH cross-linked structure formed by their interaction is denser than CSH, so the prepared cement-based material has a smaller pore size, thereby improving the mechanical properties while also enhancing the anti-permeability performance; 3) Clay and limestone are abundant and widely distributed worldwide, which can meet the needs of large-scale production; 4) LC 3 The raw materials of LC have rich adaptability advantages. About 75% of cement plants in the world only need to make minor adjustments to the production line to use the existing infrastructure to produce LC. 3 .

[0004] Chinese patents with publication numbers CN114988809A, CN117125907A, and CN111875268B respectively disclose the use of halloysite, ball clay, and residual mud to replace pure kaolinite as clay components to prepare LC 3 The method aims to solve the high cost problem caused by using pure kaolinite as raw material, and to provide 3The development of LC provides more sources of raw materials. However, none of the above patents involve the technology of cementitious material retarders or hydration aids. The literature (M.Antoni, Cement substitution by a combination of metakaolin and limestone, 2012; AAAkindahunsi, The influence of some calcined clays from Nigeria as clinker substitute in cementitioμs systems, 2020; F.Avet, Determination of the amount of reacted metakaolin in calcined clay blends, 2020) discussed the LC from the aspects of reducing the amount of clinker used, the type of calcined clay, and the content of metakaolin in the mixed system. 3 The mechanical properties and microstructure of the system are affected, but so far no efficient and low-cost hydration reaction additive has been developed to replace gypsum to achieve LC 3 Adjustment of hydration rate. In view of this, the present invention proposes a method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate, aiming to solve the problems raised in the above background technology.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate comprises the following steps:

[0008] Step 1, using polyaluminium ferric sulfate as a flocculant, washing and purifying ball clay to obtain a mixed slurry of ball clay and polyaluminium ferric sulfate, drying, grinding and calcining the mixed slurry to obtain a mixed powder of calcined ball clay and polyaluminium ferric sulfate;

[0009] Step 2: Mix 30.0-35.0% of a mixed powder of calcined ball clay and polyaluminium ferric sulfate, 15.0% of ground calcium carbonate powder and 50.0-55.0% of cement clinker in mass percentage to obtain a solid mixture;

[0010] The mixed powder of 30.0-35.0% calcined ball clay and polyaluminium ferric sulfate comprises 30.0% calcined ball clay and 0.0-5.0% polyaluminium ferric sulfate;

[0011] Step 3: Mix the solid mixture with water and stir evenly, and after curing and forming, obtain limestone calcined clay cement.

[0012] Furthermore, in step 1, the ball clay is low-grade ball clay, and the polyaluminium ferric sulfate is prepared by treating the ball clay with sulfuric acid (CN117861612A).

[0013] Furthermore, in step 1, the Al2O3 mass percentage of the polyaluminium ferric sulfate is ≥ 10.0% and the density is ≥ 1.3 g / cm 3 , the mass fraction of insoluble matter is ≤0.2%.

[0014] Furthermore, in step 1, the main components of the ball clay are 55.0% to 65.0% SiO2, 22% to 28% Al2O3 and 1.4% to 3.5% Fe2O3; and the particle size distribution of the ball clay is between 100.0 and 400.0 μm.

[0015] Furthermore, in step 2, the main component of the heavy calcium powder is CaCO3, and the content is above 95.0%; the particle size distribution of the heavy calcium powder is between 100.0 and 500.0 μm.

[0016] Furthermore, in step 2, the main components of cement clinker are composed of four minerals: tricalcium silicate (3CaO·SiO2), dicalcium silicate (2CaO·SiO2), tricalcium aluminate (3CaO·Al2O3) and tetracalcium aluminoferrite (4CaO·Al2O3·Fe2O3), and the total amount of the main components accounts for more than 95.0%; the particle size distribution of cement clinker is between 5.0 and 60.0 μm, and the specific surface area is greater than 500 m 2 / kg.

[0017] Furthermore, in step 3, the ratio of water to solid mixture is 5.0-6.0.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention adopts polyaluminum ferric sulfate as a flocculant based on the characteristic that flocculants are required in the mining, washing and sand removal of low-grade ball clay in the industrial production process, and applies the mixed slurry of low-grade ball clay and polyaluminum ferric sulfate after sedimentation to the limestone calcined clay cement system to replace the calcined clay and gypsum components in the system, which not only simplifies the production process but also brings higher economic value.

[0020] 2. In the limestone calcined clay cement system, the present invention replaces gypsum with polyaluminium ferric sulfate, which can be used as an accelerating agent and an early strength agent. Aluminium sulfate and calcium hydroxide react rapidly to generate calcium sulfonate (AFt), which improves the hydration rate of the system, greatly shortens the setting time, and enhances the early strength. At the same time, the introduction of polyaluminium ferric sulfate promotes the generation of more needle-shaped AFt phases. During the hydration process, AFt is gradually converted into monosulfur calcium aluminate hydrate, and more aluminum sources are brought to the system, generating more hydrated calcium aluminosilicate. Under the joint action of monosulfur calcium aluminate hydrate and calcium aluminosilicate hydrate, the structure of the cementitious material is more compact, which not only improves the later strength, but also enhances the resistance to ion penetration and reduces the intrusion of harmful media.

[0021] 3. The process flow of the method of the present invention is simple, and the raw materials are cheap and easily available. Ordinary Portland cement production plants only need to make simple adjustments to the production line to achieve the production of the product. This method has low actual utilization cost and high utilization value, and promotes the development of limestone calcined clay cement system. DETAILED DESCRIPTION

[0022] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0023] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0024] Example 1: Dry the mixed slurry of ball clay and polyaluminium ferric sulfate, and grind it to a specific surface area greater than 500.0 m 2 / kg and calcine at 700℃. Grind the heavy calcium powder and cement clinker separately to a specific surface area greater than 500.0m 2 / kg. In terms of mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, and 55.0% cement clinker were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed and stirred with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 The mortar test block was used as the cementitious material. It was mixed in the proportion of 450g cementitious material, 1235.3g gravel, 529.5g sand and 185g water to make a Φ100×50mm concrete test block and cured for 28d for the electric flux experiment.

[0025] Example 2: Dry the mixed slurry of ball clay and polyaluminium ferric sulfate, and grind it to a specific surface area greater than 500.0 m 2 / kg and calcine at 700℃. Grind the heavy calcium powder and cement clinker separately to a specific surface area greater than 500.0m 2 / kg. In terms of mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 54.0% cement clinker and 1.0% polyaluminium ferric sulfate were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0026] Example 3: Dry the mixed slurry of ball clay and polyaluminium ferric sulfate and grind it to a specific surface area greater than 500m 2 / kg and calcine at 700℃. Grind the heavy calcium powder and cement clinker separately to a specific surface area greater than 500m 2 / kg. In terms of mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 52.0% cement clinker and 3.0% polyaluminium ferric sulfate were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed and stirred with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0027] Example 4: Dry the mixed slurry of ball clay and polyaluminium ferric sulfate and grind it to a specific surface area greater than 500m 2 / kg and calcine at 700℃. Grind the heavy calcium powder and cement clinker separately to a specific surface area greater than 500m 2 / kg. In terms of mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 50.0% cement clinker and 5.0% polyaluminium ferric sulfate were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0028] Comparative Example 1: Grind heavy calcium powder, cement clinker, ball clay and gypsum separately to a specific surface area greater than 500m 2 / kg, and calcine the ball clay at 700℃ for 2h. By mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 54.0% cement clinker and 1.0% gypsum were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed and stirred with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0029] Comparative Example 2: Grind heavy calcium powder, cement clinker, ball clay and gypsum separately to a specific surface area greater than 500m 2 / kg, and calcine the ball clay at 700℃ for 2h. By mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 52.0% cement clinker and 3.0% gypsum were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed and stirred with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0030] Comparative Example 3: Grind heavy calcium powder, cement clinker, ball clay and gypsum separately to a specific surface area greater than 500m 2 / kg, and calcine the ball clay at 700℃ for 2h. By mass fraction, 15.0% heavy calcium powder, 30.0% calcined ball clay, 50.0% cement clinker and 5.0% gypsum were mixed evenly to obtain a mixed cementitious material. 450g of the mixed cementitious material was mixed and stirred with 1350g of standard sand, and 247.5g of water (the ratio of water to the mixed cementitious material was 0.55) was added to obtain LC 3 The mortar test blocks were cured for 3 days and 28 days respectively for strength determination. 3 Cement was used as the cementitious material and was mixed in the proportion of 450 g cementitious material, 1235.3 g gravel, 529.5 g sand, and 185 g water to make a Φ100×50 mm concrete block and cured for 28 days for the electric flux experiment.

[0031] The 3d flexural strength of the cement clinker used in Examples 1 to 4 and Comparative Examples 1 to 3 is 5.3MPa, the 3d compressive strength is 14.8MPa, the 28d flexural strength is 6.5MPa, and the 28d compressive strength is 32.6MPa. The strength test method is carried out in accordance with the national standard GB / T17617-1999 "Test method for strength of cement mortar (ISO method)"; the resistance to chloride ion penetration is measured by electric flux in accordance with the national standard GB / T50082-2009 "Standard for test method of long-term and durability performance of ordinary concrete"; the setting time is measured in accordance with the national standard GB / T1346-2011 "Test method for water consumption, setting time and stability of cement standard consistency". The test results are shown in Table 1 below:

[0032] Table 1. LC prepared in Examples 1 to 4 and Comparative Examples 1 to 3 3 Performance test results of mortar and concrete test blocks

[0033]

[0034] The results show that: LC using polyaluminium ferric sulfate as an accelerating agent 3 The initial setting time of the mortar test block was greatly reduced, and the initial setting time in Example 3 was shortened to 76 minutes. In addition, compared with the sample using gypsum, the LC using polyaluminum ferric sulfate as the early strength agent 3 The compressive and flexural strengths of the mortar specimens were higher at 3 days. At the same time, the electric flux performance of the concrete specimens made of it also showed advantages at 28 days. Although the chloride ion permeability coefficients were not much different, in general, the LC using polyaluminum ferric sulfate as an accelerating agent and early strength agent was better. 3 Low carbon cement (LC 3 The comprehensive performance of mortar test blocks and concrete test blocks has shown great advantages.

[0035] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate, characterized in that: The following steps are involved: Step 1, using polyaluminium ferric sulfate as a flocculant, washing and purifying ball clay to obtain a mixed slurry of ball clay and polyaluminium ferric sulfate, drying, grinding and calcining the mixed slurry to obtain a mixed powder of calcined ball clay and polyaluminium ferric sulfate; Step 2: Mix 30.0-35.0% of a mixed powder of calcined ball clay and polyaluminium ferric sulfate, 15.0% of ground calcium carbonate powder and 50.0-55.0% of cement clinker in mass percentage to obtain a solid mixture; The mixed powder of 30.0-35.0% calcined ball clay and polyaluminium ferric sulfate comprises 30.0% calcined ball clay and 0-5.0% polyaluminium ferric sulfate; Step 3: Mix the solid mixture with water and stir evenly, and after curing and forming, obtain limestone calcined clay cement.

2. The method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate according to claim 1, characterized in that: In step 1, the Al2O3 mass percentage of the polyaluminium ferric sulfate is ≥ 10.0% and the density is ≥ 1.3 g / cm 3 , the mass fraction of insoluble matter is ≤0.2%.

3. The method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate according to claim 1, characterized in that, In the step 1, the main components of the ball clay are 55.0% to 65.0% SiO2, 22% to 28% Al2O3 and 1.4% to 3.5% Fe2O3; the particle size distribution of the ball clay is between 100.0 and 400.0 μm.

4. The method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate according to claim 1, characterized in that: In step 2, the main component of the heavy calcium powder is CaCO3, and the content is above 95.0%; the particle size distribution of the heavy calcium powder is between 100.0 and 500.0 μm.

5. The method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate according to claim 1, characterized in that: In step 2, the main components of cement clinker are composed of four minerals: 3CaO·SiO2, 2CaO·SiO2, 3CaO·Al2O3 and 4CaO·Al2O3·Fe2O3, and the total amount of the main components accounts for more than 95.0%; the particle size distribution of cement clinker is between 5.0 and 60.0 μm, and the specific surface area is greater than 500 m 2 / kg.

6. The method for preparing limestone calcined clay cement based on polyaluminium ferric sulfate according to claim 1, characterized in that: In the step 3, the ratio of water to solid mixture is 5.0-6.0.

Citation Information

Patent Citations

  • Calcined clay and its preparation method and limestone calcined clay cement

    CN111875268B

  • Method for preparing limestone calcined clay cement from halloysite

    CN114988809A

  • Porous aluminum ferric sulfate flocculant prepared from ball clay and cleaning process method

    CN117861612A

  • Calcined clay type sulphoaluminate cement gel material

    CN108383403A

  • Novel LC3 material prepared based on ball clay and preparation method thereof

    CN117125907A